Prevalence of patients with self‐reported hidradenitis suppurativa in a cohort of Danish blood donors: a cross‐sectional study. (20th September 2018) - Theut Riis, P.; Pedersen, O.B.; Sigsgaard, V.; Erikstrup, C.; Paarup, H.M.; Nielsen, K.R.; Burgdorf, K.S.; Hjalgrim, H.; Rostgaard, K.; Banasik, K.; Ullum, H.; Jemec, G.B.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease characterized by recurrent inflamed nodules. No pathognomonic test is available for HS; hence the diagnosis is based on three clinical criteria. Objectives: To estimate the cross‐sectional prevalence and characterize patients with HS in the Danish Blood Donor Study cohort. Methods: A questionnaire previously developed containing HS screening questions, the Major Depression Inventory, the Short Form‐12, as well as questions about height, weight and drinking habits was answered by 27 765 blood donors. Results: The prevalence of HS was 1·8% [95% confidence interval (CI) 1·6–2·0%] in the cohort of Danish blood donors. Donors with HS were on average 4·7 years younger ( P < 0·001), had 1·3 kg m −2 higher mean body mass index (BMI) ( P < 0·001) and were significantly more likely to smoke [odds ratio (OR) 1·44, 17·9% vs. 13·1%, P = 0·002] compared with donors without HS. Furthermore, significantly more donors with HS were classified as having moderate depression (3·2% vs. 0·7%, P < 0·001). Also, significantly more patients with HS were apprenticeship educated, received educational support and sickness or cash benefits. Conclusions: The prevalence of HS in the cohort of blood donors was estimated to 1·8% (95% CI 1·6–2·0%). Donors with HS reported characteristics similar to those reported for hospital‐based patients with HS such as higher BMI, smoking rates and lower socioeconomic status than donors without HS. Abstract : What's already known about this topic? The population prevalence of hidradenitis suppurativa (HS) is estimated at between 1% and 4%. It is suspected that patients with HS have a lower socioeconomic status. Patients with HS are prone to depression and anxiety. What does this study add? The prevalence of HS in a population of Danish blood donors was estimated to be 1·8% (95% confidence interval 1·6–2·0%). Blood donors with HS have a lower socioeconomic status based on job description, but HS does not seem to affect personal income, after adjusting for age and sex. HS increases the risk of depression, even in a cohort of presumably mildly affected blood donors. Linked Comment: Shalom and Cohen. Br J Dermatol 2019;180 :712–713 . Respond to this article Plain language summary available online